Compositional characteristics and nutritional quality of Eurasian beaver (Castor fiber) meat - V. Razmaitė; R. Šveistienė; G.J. Švirmickas (Czech Journal of Food Sciences, 2011)
The meat of Eurasian beaver (Castor fiber) as obtained in Lithuania contained 21.4% crude protein with high amounts of glutamic acid (152.6 mg/g), aspartic acid (87.6 mg/g), lysine (81.8 mg/g), leucine (75.7 mg/g), arginine (60.4 mg/g), and isoleucine (60.1 mg/g). This meat could be a high quality protein source because of its well-balanced essential amino acid composition. Polyunsaturated fatty acids were predominant with a percentage of 41.58% in thighs and of 42.12% in the fat depot of tails. Hexadecanoic acid (C16:0) was the dominant fatty acid in thigh muscles, followed by octadecadienoic (C18:2n-6), octadecenoic (C18:1), and octadecatrienoic (C18:3n-3) acids with the percentages 23.05, 22.66, 22.28, and 12.40, respectively. In the tail lipids, the dominant fatty acid was C18:1, followed by C18:3n-3 and C18:2n-6, and C16:0 with the percentages 31.72, 21.87, 18.53, and 12.96, respectively. With predominant polyunsaturated fatty acids and an n-6/n-3 PUFA value 2.1, beaver meat could be n-3 PUFA-rich food in human diets.